Temporal variations of body mass and plumage in Arenaria interpres (Aves: Scolopacidae) along the Brazilian coast - Rodrigues,Roberta C. (2009)
Every year, Brazil receives large flocks of nearly 40 migratory shorebirds species. The accumulation of body fat and nutrients during the summer is necessary for the long return flights of these birds and is fundamental for feather moulting and the change of their plumage. We present here an examination of the relationship between body mass and plumage change in Arenaria interpres (Linnaeus, 1758), one of those birds, over time during its wintering period on the Brazilian coast. We analyzed information collected at five traditional stopover sites along the Brazilian coast, between 1997 and 2007. During the month of September, individuals with intermediate or breeding plumage had smaller body masses as compared to other months. From October to December, adult individuals were only observed with eclipse plumage and had average body masses of approximately 100 g. In March, individuals with intermediate, eclipse and breeding plumages were recorded, but their average body mass remained at approximately 100 g. In April and May the numbers of individuals with breeding or intermediate plumage increased, and they showed significant increases in body mass at a rate of approximately 1.5 and 2.3 g per day, in the north-northeastern and south coast, respectively, leading to an average mass of 124 and 143g in these months. That is suggested to be the departure mass of A. interpres in the Brazilian north-northeastern and south coast, respectively, when starting the migration to the breeding sites.